Drug eruptions and hepatic involvement: a study - Manne, Vimala; Pinjala, Padmaja (International Journal of Research in Dermatology, 2018)
Background: Assessment by liver biopsy remains the gold standard in defining drug induced liver disease. Liver biopsy is an invasive procedure. Hence, a technique that is simpler is required to detect drug induced liver dysfunction. The profile of liver function tests (LFT) abnormalities, provides an initial guide to the clinical syndrome of drug induced hepatotoxicity. This study attempts to draw a possible correlation as well as to derive insight into the involvement of liver in drug eruptions through simple liver function tests. Methods: 112 cases of patients with drug rash whom we have a tendency to saw within the department of medicine as out-patients and in-patients since 2015 to 2018 in Osmania General Hospital, Katuri Medical College and Hospital and Dr. V. R. K Women’s Medical College, Teaching Hospital and Research Centre were enclosed during this study. Total number of cutaneous drug rash cases enrolled: 83 Total number of drug rash cases with Liver Function Test abnormalities: 17. Results: Out of 83 patients of drag rash 20% (17) had liver function test abnormalities while 80% (66) had normal hepatic function. Out of 17 drug rash cases with liver function test abnormalities 35% (6) were between 4-14 years of age group. Out of 17 drug rash cases with liver function test abnormalities 70.6% (12) were males and 29.4% (5) were females. Conclusions: To conclude, a sound knowledge of morphological patterns of drug rashes with hepatic involvement, drugs implicated in causing drug rashes and hepatic dysfunction and an easy detection of impending danger by the simple biochemical tests (liver function tests) can evert a major crisis and thus help the clinicians to better manage their cases.